Mesoporous TiO2/Carbon Beads: One-Pot Preparation and Their Application in Visible-Light-Induced Photodegradation - Li, Xiaowei; Jiang, Yanqiu; Cheng, Wenjing; Li, Yudong; Xu, Xianzhu; Lin, Kaifeng (Nano-Micro Letters, 2015)
Mesoporous TiO2/Carbon beads have been prepared via a facile impregnation-carbonization approach, in which a porous anion-exchange resin and K2TiO(C2O4)2 were used as hard carbon and titanium source, respectively. Characterization results reveal that the self-assembled composites have disordered mesostructure, uniform mesopores, large pore volumes, and high surface areas. The mesopore walls are composed of amorphous carbon, well-dispersed and confined anatase or rutile nanoparticles. Some anatase phase of TiO2 was transformed to rutile phase via an increase of carbonization temperature or repeated impregnation of the resin with TiO(C2O4) 2−2 species. X-ray photoelectron spectroscopy, carbon, hydrogen, and nitrogen element analysis, and thermal gravity analysis results indicate the doping of carbon into the TiO2 lattice and strong interaction between carbon and TiO2 nanoparticles. A synergy effect by carbon and TiO2 in the composites has been discussed herein on the degradation of methyl orange under visible light. The dye removal process involves adsorption of the dye from water by the mesopores in the composites, followed by photodegradation on the separated dye-loaded catalysts. Mesopores allow full access of the dye molecules to the surface of TiO2 nanoparticles. Importantly, the bead format of such composite enables their straightforward separation from the reaction mixture in their application as a liquid-phase heterogeneous photodegradation catalyst.